(untitled) - Kozak, Simon (Doprava a spoje, 2005)
The aim of the article is to present a significance of evaluation of externality with evaluation of economic efficiency of investments and decision of investments. An article dealt with evolution of transports in Slovak Republic and individual external cost types in Europe and Slovak Republic. It next analyses gross domestic product of Slovakia and rates proportion in GDP of external cost. In three chapter is shows data of application of external cost to method of evaluation of economic efficiency of investments NPV (Net Present Value).